Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/app10093158
|View full text |Cite
|
Sign up to set email alerts
|

Double B-Spline Curve-Fitting and Synchronization-Integrated Feedrate Scheduling Method for Five-Axis Linear-Segment Toolpath

Abstract: The discontinuities of a five-axis linear-segment toolpath result in fluctuation in the feedrate, acceleration and jerk commands that lead to machine tool vibration and poor surface finish. For path smoothing, with the global curve-fitting method it is difficult to control fitting error and the local corner-smoothing method has large curvature extreme. For path synchronization, the parameter synchronization method cannot ensure smooth rotary motion. Aiming at these problems, this paper proposes a double B-spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Another source of vibration in five-axis machining is the discontinuities of the linear-segment toolpath inducing fluctuation in the programmed feed rate. Gao et al [5] proposed a double B-spline curve-fitting and synchronization-integrated feed rate scheduling method. They experimentally concluded that this method generates a smooth toolpath with an allowable fitting error.…”
Section: Devices and Experimental Techniquesmentioning
confidence: 99%
“…Another source of vibration in five-axis machining is the discontinuities of the linear-segment toolpath inducing fluctuation in the programmed feed rate. Gao et al [5] proposed a double B-spline curve-fitting and synchronization-integrated feed rate scheduling method. They experimentally concluded that this method generates a smooth toolpath with an allowable fitting error.…”
Section: Devices and Experimental Techniquesmentioning
confidence: 99%
“…B-spline curve approximation has been a hot research topic in the field of computeraided geometric design in recent years. With the development of computer-aided design (CAD) and the rise of advanced manufacturing technology, B-spline is widely used in the design and manufacturing industry of free curves and surfaces [1][2][3][4][5]. In the field of shipbuilding, the design of ship lines is the basis of shipbuilding [6].…”
Section: Introductionmentioning
confidence: 99%
“…B-spline curve fitting [19][20][21][22][23] is an approach that performs a nonlinear fit of data based on a limited selection of these data. As the B-spline curve method is a simple calculation procedure with fast calculation speed and geometric invariance, it is widely used in engineering practice, such as for the geometric definition of various industrial products and nonlinear curve reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…As the B-spline curve method is a simple calculation procedure with fast calculation speed and geometric invariance, it is widely used in engineering practice, such as for the geometric definition of various industrial products and nonlinear curve reconstruction. Gao et al [20] proposed a double B-Spline curve fitting and synchronization-integrated federate scheduling method for a Five-Axis linear-segment tool path, and simulation showed that this method can generate a smooth tool path and constrain the fitting error. Xu et al [21] rebuilt the strain field of multiple elements by using the B-spline curve and inverse finite element methods to prove that the proposed algorithm can significantly improve the accuracy of reconstruction displacement.…”
Section: Introductionmentioning
confidence: 99%